Conceptualizing Nature as a Legal Subject: A Comparative Study of Laws Between Indonesia, New Zealand, and Ecuador - Fadillah, Muhamad Akmal; Azhari, Aidul Fitriciada (Universitas Semarang, 2024)
This paper aims to find out the extent to which Indonesia views the concept of nature as a legal subject. This research can provide comprehensive information and understanding, which focuses on comparative law and how the application of the Theory of Legal Transplantation. Two experiences have occurred, namely in New Zealand and Ecuador, which have answered the view of nature as a legal subject. Based on these two experiences, it becomes urgent in the preparation of this research to describe the concept of nature as a legal subject in Indonesia by comparing Indonesian regulations on environmental protection and examining how Indonesia views the concept of nature as a legal subject through the existing legal system, as well as definitive legal subjects. The method used is normative juridical with a comparative approach and conceptual approach. The writing of this legal Article has the novelty of discussing the application of Articles 66 and 91 of Law Number 32 of 2009, which explicitly discusses the concept of nature as a legal subject in Indonesia and the view of Legal Transplantation Theory. The results of this study indicate that Indonesia's Law on environmental protection still does not need to recognize nature as a legal subject. Still, with the experience of two countries that have accommodated nature as a legal subject, it is not impossible through Legal Transplantation Theory that the influence in the form of legal instruments or concepts can be transplanted to the Indonesian State as a source of environmental protection regulation formation.